FINANCIAL INDEPENDENCE STRATEGY WITH THE ROLE OF SOCIAL CAPITAL AND HUMAN CAPITAL: MEDIATION OF INNOVATION ABILITY OF FISHERMEN GROUP ON BALEKAMBANG COAST, EAST JAVA - Ayu Agus Tya Ningsih; Sukma Perdana (RADJA PUBLIKA, 2025)
The study aims to elucidate the implications derived from analyzing the direct effects of social capital and human capital on financial independence and innovation, as well as the impact of innovation on financial independence. Furthermore, it elucidates the significance and examination of the impact of social capital and human capital, mediated by innovation, on financial independence. The analytical instrument employed is a structural equation model utilizing Partial Least Squares, accompanied by a mediation test via Sobel. The study sample comprised 52 members of the Kondang Merak Beach fishermen's organization in Balekambang, East Java, Indonesia. The study's findings indicate that social capital does not directly influence financial independence; nevertheless, human capital has a direct and significant impact on both financial independence and innovation. Innovation directly influences financial independence. Innovation cannot mediate the impact of social capital; nevertheless, it can mediate the effect of human capital on financial independence.